Anatomic Considerations for Sciatic Nerve Block in the Popliteal Fossa Through the Lateral Approach. Issue 5 (September 1996) - Vloka, Jerry D.; Hadžić, Admir; Kitain, Eric; Lesser, Jonathan B.; Kuroda, Max; April, Ernest W.; Thys, Daniel M.
Abstract : Background and Objectives: The disadvantage of the classic posterior approach to block of the sciatic nerve at the knee level (popliteal nerve block [PNB]) is the need to position a patient in the prone position for performance of the block. In this study on cadavers, a lateral approach to the popliteal nerve in the supine position was investigated, and some anatomic considerations of relevance to popliteal nerve block were addressed. Methods: In 19 cadaver right legs, the lateral approach to PNB was simulated with a needle, introduced in the groove between the biceps femoris and vastus lateralis muscles 7 cm above the knee, at either 30° or 60° relative to the horizontal plane, and 1 mL of dye solution was injected through the needle. After dissection of the popliteal fossa, the position of the solidified bolus of dye in relation to the popliteal nerve was determined. Additionally, the dye was injected into the popliteal nerve sheath, and the spread of the dye and continuity of the sheaths were determined. Results: In 10 legs, the lateral approach was attempted at a 30° angle and in 9 legs at a 60° angle. The solidified injectates at 30° were closely distributed anterolaterally to the nerve, while injectates at 60° tended to be further from the nerve and scattered along its posterolateral aspect ( P = .02). The dye injected into the nerve sheaths traveled 5 to 10 cm within the sheath, surrounding both main divisions of the popliteal nerve, the tibial and the common peroneal nerve. Conclusion: A lateral approach to the popliteal nerve with insertion of the needle at a 30° angle relative to the horizontal plane results in predictable approximation of the needle tip to the popliteal nerve. The results also suggest the existence of a continuous neural sheath encompassing the popliteal nerve and its main branches. This may have clinical implications similar to those in perivascular neuronal block.